Exclusion and the growth of AI technology: a trade-theoretic analysis - Hazari, Bharat; Mohan, Vijay (Frontiers in Human Dynamics, 2024)
This study provides a four-good general equilibrium framework with international trade for assessing the impact of the advancement of automation and artificial intelligence (A&AI) on the welfare of a group of agents who are excluded from both owning productive assets, such as capital and land, as well as consuming digital output (digital exclusion). We show that, depending on the magnitude of the factor intensities, the accumulation of A&AI capital may negatively affect the income of the excluded group, who provide unskilled labor, or the owners of land. In doing so, we bring out the conflict of interests that may arise between the owners of A&AI capital and other groups within society, which has implications for the pressure that exists to slow down the adoption of A&AI in an economy.